Study of Reproductive Biological Aspects of Cetol Fish Poecilia reticulata was Caught in Freshwater of Magelang Regency - Rochvita, Ana; Anggraini, Rr. Citra P. Kusuma; Permadi, Jefri; Hamam, Faisal Nur; Firdaus, Syafrizal Akbar (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
This research aims to determine aspects of cetol fish reproductive biology including sexuality, sex ratio, GSI, gonadal maturity (TKG), and fecundity, in order to obtain information as a basis for cultivation. Samples were taken in 6 waters in the Magelang Regency area, during August at 1 week intervals. The data obtained is presented in the form of tables and figures, analyzed descriptively. Water quality is classified as good, temperature range 22.5-29.8 Â°C, pH 6.09-6.80, and DO 7.0-15.7 mg/L. Cetol fish have sexual dimorphism and dichromatism. The male:female sex ratio is 1.1:1. Male and female fish in TKG I-VI, with a greater percentage of males and females in TKG III-VI than in TKG I-II. At a length of 1.6-2.0 cm, males have been found in TKG III-V and females in TKG III-IV, and at a length of 2.1-2.5 cm, males and females have been found in TKG III-VI. The GSI of male fish reaches 8.22% (1.2-2.5 cm) and for females it reaches 28.09% (1.1-3.8 cm). Fecundity ranges from 2-36 eggs (1.1-3.8 cm and 0.07-0.57 g). The conclusion of this research is that the sex ratio is unequal, male and female cetol fish first mature gonads at a length of 1.6-2.0 cm, and females can give birth to young at a length of 2.1-2.5 cm. August is the spawning season for cetol fish marked by high GSI and TKG advanced. Cetol fish are viviparous so fecundity is low.